Phenolic profiles and antioxidant properties of Physalis angulata L. as quality indicators - Marcos Cobaleda-Velasco; Ruth E. Alanis-Bañuelos; Norma Almaraz-Abarca; Marlon Rojas-López; Laura S. González-Valdez; José A. Ávila-Reyes; Sara Rodrigo (GarVal Editorial Ltda., 2017)
Context: Previous reports informed about the species-specific condition of plant phenolic profiles and the association between phenolic composition and plant antioxidant properties. The species-specific condition of phenolic patterns offers the opportunity to develop chemical quality markers for plants used in traditional medicine. However, changes in phenolic composition can occur during plant growth. Physalis angulata is an important medicinal plant for which the age-related variation of phenolic composition and antioxidant properties is unknown. Aims: To assess the phenolic composition and antioxidant properties of above- and under-ground parts of P. angulata at four growth stages and evaluate their potential as chemical quality indicators. Methods: A method of HPLC-DAD was used to assess the phenolic profiles. Anti-radical potential, total antioxidant capacity and iron reducing power were evaluated by spectrometric methods. Sample distinctiveness was determined by cluster analyses. Results: The HPLC-DAD analysis revealed 21 phenolic compounds, which were accumulated in a tissue- and age-specific manner. On the contrary, a clear distinctiveness between phenolic contents and antioxidant properties of samples was not observed. Mature flowers highlighted for its total phenolic content (6.50 mg/g fresh tissue) and total antioxidant capacity (416.1 µg/mL). Young leaves were outstanding for its flavonoid content (37.86 µg/g fresh tissue) and reducing power (A700nm = 4.04). Immature calyces were worthy for its phenolic acid concentration (1.28 µg/g fresh tissue) and its free radical scavenging activity (EC50 = 0.12 mg/mL). Conclusions: Phenolic profiles represent reliable chemical quality indicators for determining plant age, tissular origin, authenticity, and adulteration of herbal preparations of P. angulata.